Functional Constipation and Dyssynergic Defecation in Children - Koppen, Ilan J. N.; Benninga, Marc A. (Frontiers in Pediatrics, 2022)
Defecation is a complex physiologic process which relies on intricate mechanisms involving the autonomic and somatic nervous system, pelvic floor muscles, and both the internal and external anal sphincters. Anorectal dysfunction may result in constipation, a bothersome defecation disorder which can severely impact daily lives of children and their families. In this review, we provide an overview of pathophysiological mechanisms underlying functional constipation in children. We focus on different mechanisms underlying anorectal dysfunction and specific treatment options aimed at improving defecation dynamics in children.